Penerapan Reward And Punishment Dalam Meningkatkan Disiplin Guru di SMP Negeri 1 Pelepat Ilir - Dyah Ayu Sapto Rini (NUR EL-ISLAM : Jurnal Pendidikan dan Sosial Keagamaan, 2020)
Improving the quality of learning in school is very dependent on several factors. One of them, the improvement of good culture in schools. School culture is a positive thing that must be maintained and implemented by all school residents without feeling compelled. One of the culture of schools that must be maintained is the problem of discipline, including the discipline of the teachers in attending class in the teaching and learning process. As a figure who is always modeled after his behavior, the timely attendance of teachers in class is a clear example of discipline that will be seen and even emulated by students. This study aims to describe the improvement of teacher discipline in teaching presence in the classroom through the application of Reward and Punishment. This research is a case study using a qualitative approach. The research subjects were educators in SMPN 1 Pelepat Ilir. The method used in this study is the School Action Research (PTS) method. The results achieved from this study are that the application of Reward and Punishment is effective for increasing the discipline of teacher presence in class in teaching and learning activities.